Plant growth-promoting rhizobacteria (PGPR) improve the growth and nutrient use efficiency in maize (Zea mays L.) under water deficit conditions. Issue 10 (October 2020) - Pereira, S.I.A.; Abreu, D.; Moreira, H.; Vega, A.; Castro, P.M.L.
Abstract: Drought is one of the major abiotic stresses that affects crop yield worldwide. An eco-friendly tool that can broadly improve plants' tolerance to water stress is bioionocula comprising plant growth-promoting rhizobacteria (PGPR). In this study, the effect of two PGPR Cupriavidus necator 1C2 (B1) and Pseudomonas fluorescens S3X (B2), singly and/or co-inoculated at two inocula sizes (S1 - 3 × 10 3 cells g −1 dry weight (dw) soil and S2 - 3 × 10 6 cells g −1 dw soil), on growth, nutrient uptake, and use efficiency was assessed in maize ( Zea mays L.) plants grown at three levels of irrigation (80% of water holding capacity (WHC) – well-watered, 60% of WHC - moderate water deficit stress, and 40% of WHC - severe water deficit stress) in a greenhouse experiment. The impact of water deficit and bioinoculants on soil microbial activity (fluorescein diacetate hydrolysis) was also evaluated. Moderate and severe water deficit negatively affected soil microbial activity, as well as, maize growth, by reducing plants' shoot biomass and increasing root/shoot ratio at 60 and 40% of WHC. Bioinoculants mitigated the negative effects on shoot biomass, especially when PGPR were co-inoculated, increasing up to 89% the aerial biomass of plants exposed to moderate water deficit. Bioinoculation also increased nitrogen (N) and phosphorous (P) use efficiency, which may have led to higher maize growth under water deficit conditions. The size of the inocula applied had marginal influence on biometric and nutrient parameters, although the higher concentration of the mixture of PGPR was the most effective in improving shoot biomass under moderate water deficit. This study shows that rhizobacterial strains are able to increase nutrient use efficiency and to alleviate water stress effects in crops with high water demands and have potential applications to keep up with productivity in water stress scenarios. Abstract : Agricultural sciences; Biotechnology; Microbiology; Bioinoculants; Drought; Inocula size; Water deficit; Water scarcity; Agricultural soil science; Agricultural water management; Crop biomass; Microbial biotechnology; Nutrient availability